Enlivening the effect of tourists' knowledge and involvement on Malaysian Heritage Food (MHF) towards food tourism image in Malaysia - Omar, Siti Radhiah; Ab Karim, Shahrim; Isa, Siti Suriawati; Omar, Siti Nazirah (I G I Global, 2019)
This current article aims to empirically test the relationship between international tourist knowledge and Malaysian Heritage Food (MHF) cultural involvement on Malaysia's Food Tourism Image and secondly, to analyze the mediating effect of knowledge for both relationships. A quantitative survey of 719 international tourists with previous MHF consumption experience was conducted and analyzed via a Structural Equation Modeling (SEM) approach. Results demonstrated that the following variables have significant associations with Food Tourism Image while knowledge mediated the subsequent links positively with partial mediation. Regardless of the theoretical and managerial implications and research findings, supplementary investigations are warranted to enhance the growth of food cultural tourism.